Shared Value and Pain Value of Consumers Towards The Purchase of Bango Sweet Soy Sauce Using Ethnographic Methods (Case Study of Berkah Azzahra Shop) - Era Pamadia; Syarifudin Syarifudin; Jerry Heikal (Eduvest - Journal of Universal Studies, 2025)
In the increasingly competitive soy sauce market, consumer loyalty and satisfaction are challenged by product quality, packaging issues, and corporate social responsibility. Despite Bango sweet soy sauce’s strong brand presence, limited research has analyzed consumers’ shared values and pain through an ethnographic lens. This study aims to explore how Bango creates shared value and addresses consumer pain points during purchase experiences. Using a realistic ethnographic method, the study involved participant observation and in-depth interviews with five consumers at the Berkah Azzahra store. Findings reveal that shared value is driven by Bango’s commitment to empowering local soybean farmers, promoting environmental sustainability, and fostering emotional brand connections. Meanwhile, pain value is associated with packaging issues, particularly leaky plastic packaging that affects product hygiene and consumer convenience. These insights highlight the importance of maintaining product authenticity while addressing practical consumer concerns. The study implies that continuous improvements in packaging, alongside strengthened CSR programs, can enhance consumer trust and loyalty. For companies like Unilever, this research offers a strategic foundation to refine marketing and product development initiatives based on real consumer experiences.